Engineering of LysR-type Regulator DmlR in Burkholderia ubonensis CP01 to Enhance Its Antifungal Production against Ganoderma boninense - Budinarta, Widyah; Purnamasari, Maria Indah; Hermosaningtyas, Anastasia Aliesa; Arifudin Rafif , Muhammad Ghildan; Prihatna , Cahya; Suwanto, Antonius (Bogor Agricultural University, Indonesia, 2026)
The utilization of an antifungal substance, occidiofungin and burkholdine, derived from Burkholderia ubonensis CP01 has displayed promising results in the management of basal stem rot caused by Ganoderma boninense. The study aims to further enhance the antifungal production of B. ubonensis CP01 through genetic modification. Through comparative genetic analysis, we identified the dmlR gene in B. ubonensis CP01, which is homologous to the scmR gene, a LysR-type transcriptional regulator (LTTR), in B. thailandensis. Deleting the dmlR gene in CP01 resulted in a complete loss of antifungal synthesis. In contrast, overexpression of this gene led to a substantial increase in antifungal production, as determined by an agar well diffusion assay. These findings suggest that dmlR acts as a positive regulator of antifungal gene expression in B. ubonensis CP01. RP-HPLC analysis revealed that the mutant strain overexpressing the dmlR gene (mutant WB12) produced a higher peak at the 24-25 minute elution time. Previous high-resolution mass spectrometry analysis by our group identified the compound at this peak as six analog compounds with monoisotopic masses similar to those of cyclic lipopeptides, including occidiofungin and burkholdine. The WB12 mutant exhibited approximately 15% higher concentrations of antifungal compounds than the wild type. Additionally, whole genome sequencing confirmed that the introduced dmlR gene had been integrated into the locus on chromosome 2 of B. ubonensis CP01. LTTRs play a pivotal role in regulating the production of antifungal agents in CP01. Furthermore, it highlights the potential for manipulating LTTRs to enhance the desirable characteristics of the Burkholderia genus in regard to the production of secondary metabolites.